Shared reading as an intervention to improve health and well-being in adults: a scoping review - Järvholm, Kajsa; Ohlsson, Anders; Bernhardsson, Katarina; Gustafsson, Anna W.; Johnsson, Per; Malmström, Martin; Wistrand, Jonatan; Forslid, Torbjörn (Frontiers in Psychology, 2025)
BackgroundShared reading (SR) is a group reading concept consisting of weekly meetings led by a trained facilitator where literary fiction and poetry is read aloud and discussed. SR requires no previous knowledge or homework and has been tried out as a health intervention to different vulnerable populations.ObjectivesThe present study undertook a scoping review of research evaluating SR as an intervention to improve health and/or well-being in adults. The aim was to map the existing knowledge, identify research gaps, and suggest how these gaps can be addressed in future research.MethodWe followed the PRISMA guidelines for scoping reviews. Online data bases were searched for publications on SR published between Jan 1, 2005, and Dec 31, 2024. Studies were eligible if they used SR as an intervention for adults, reported outcomes for health and/or well-being, and were published in Danish, English, Norwegian, or Swedish in peer-reviewed journals. Quantitative, qualitative, and mixed-methods studies could be included.ResultsThe search returned 179 records. We identified 15 studies, all written in English, that met the inclusion criteria. The studies were conducted in UK (67%; n = 10) and in the Scandinavian countries (33%; n = 5). Participants were mostly vulnerable populations such as people with dementia, mental illness, or chronic pain. The number of included participants varied between 4 and 61. Quantitative data were reported in 47% (n = 7) of the studies, showing improvements in quality of life and well-being and reduced symptoms of depression. Most quantitative studies were limited by small sample sizes and lack of comparison. All but one study (n = 14; 93%) reported qualitative outcomes. The qualitative data showed that the group community was a valued aspect, and participants reported positive outcomes related to health and well-being. In-depth analysis found that participation in SR groups may lead to a renewed sense of personal identity and improved capacity for mentalization.ConclusionSR was reported to be a feasible and promising intervention for several groups in different settings. However, available evidence is limited, and research gaps exist. Current findings can serve as a foundation for future studies with larger samples and longer follow-up.